2020
DOI: 10.1136/bmjsem-2020-000799
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal pain is common in competitive gaming: a cross-sectional study among Danish esports athletes

Abstract: ObjectivesThe interest for competitive esports is growing. Little is known regarding musculoskeletal (MSK) pain among esports athletes. We aimed to investigate (1) the prevalence of MSK pain, (2) the association between MSK pain and esports-related training volume and (3) the association between MSK pain and physical activity levels.MethodsAthletes aged 15–35 years who participated in structured esports through a computer-based game were eligible for inclusion. Participant demographics, hours/week spent on esp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
51
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(68 citation statements)
references
References 11 publications
13
51
2
2
Order By: Relevance
“…Esports are considered as a form of sport that has had a great development in recent years (Hamari & Sjöblom, 2017;Kane & Spradley, 2017;Jenny et al, 2017), it has seen an increase in the number of people who perform them and the interest in competitive esports is growing (Lindberg et al, 2020), its main characteristic is based on the practice facilitated by electronic systems, another factor to consider is that in this discipline athletes compete connected to the internet in different locations around the world (Bayrakdar et al, 2020). From an organizational point of view, the competition systems are regulated worldwide (Bayrakdar et al;Jenny et al, 2017) and competitions are broadcast globally thanks to the media, promoting the games and players involved (Martorell Castellano & Rom Rodríguez, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Esports are considered as a form of sport that has had a great development in recent years (Hamari & Sjöblom, 2017;Kane & Spradley, 2017;Jenny et al, 2017), it has seen an increase in the number of people who perform them and the interest in competitive esports is growing (Lindberg et al, 2020), its main characteristic is based on the practice facilitated by electronic systems, another factor to consider is that in this discipline athletes compete connected to the internet in different locations around the world (Bayrakdar et al, 2020). From an organizational point of view, the competition systems are regulated worldwide (Bayrakdar et al;Jenny et al, 2017) and competitions are broadcast globally thanks to the media, promoting the games and players involved (Martorell Castellano & Rom Rodríguez, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Studies were mainly cross sectional, with the exception of one experimental study [ 26 ]. Out of the four possible video gaming devices (computers, consoles, handhelds, smartphones), seven studies included one device [ 25 , 26 , 33 37 ], three studies included two devices [ 38 40 ] and six studies included three or more devices [ 41 – 46 ]. Due to insufficient information, it is not possible to rule out that in two studies [ 37 , 39 ] more than the indicated devices were used.…”
Section: Resultsmentioning
confidence: 99%
“…The main body regions of reported musculoskeletal pain were the neck ( n = 7), back ( n = 6), shoulders ( n = 5) and hands ( n = 5). As the evaluation method, in eleven of the studies self-designed non-standardized questionnaires were used [ 25 , 36 39 , 41 – 46 ]. Moreover, in two studies standardized questionnaires or checklists were used [ 33 , 40 ] and one study each involved the use of electromyography (EMG) data and a visual analog scale [ 26 ], a clinical test and a partially standardized questionnaire [ 34 ] or only a partially standardized questionnaire [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The symptoms that usually felt in the neck muscles include intermittent pain, tightness, or spasm, yet these would not interfere with the daily activities. 7 Playing a duration of 13-18 months had a moderate prevalence of pain, possibly caused by a longer and larger loading on the neck muscles than 6-12 months that caused muscle tightness that refers to pain. The pain interfered with daily activities, but it usually still might be controlled.…”
Section: Discussionmentioning
confidence: 99%